2022
DOI: 10.1007/s11121-022-01464-3
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Implementation Enhancement Strategy to Increase the Yield of Training and Consultation for School-Based Behavioral Preventive Practices: a Triple-Blind Randomized Controlled Trial

Abstract: Background : As the most common setting where youth access behavioral healthcare, the education sector frequently employs training and follow-up consultation as cornerstone implementation strategies to promote the implementation of evidencebased practices (EBPs). However, these strategies alone are not sufficient to promote desirable implementation (e.g., intervention fidelity) and youth behavioral outcomes (e.g., mitigated externalizing behaviors). Theory-informed pragmatic preimplementation enhancement strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…For instance, school consultants can designate influential members in the building as "implementation champions" to share publicly with colleagues the importance and benefits of SWPBIS for their work and student outcomes. School leaders can prioritize their implementation-specific leadership behaviors (e.g., effective and proactive communication and support for SWPBIS) while adopting policies and practices that foster an implementation-specific climate that explicitly encourages and rewards the delivery of SWPBIS (Zhang et al, 2022). More research is needed to develop more school-level theory-informed implementation strategies to promote staff's shared supportive beliefs about EBPs that entail school-level implementation, although emerging research exists on such implementation strategies at the individual level.…”
Section: Mediational Mechanism Of Change Underlying Educators' Belief...mentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, school consultants can designate influential members in the building as "implementation champions" to share publicly with colleagues the importance and benefits of SWPBIS for their work and student outcomes. School leaders can prioritize their implementation-specific leadership behaviors (e.g., effective and proactive communication and support for SWPBIS) while adopting policies and practices that foster an implementation-specific climate that explicitly encourages and rewards the delivery of SWPBIS (Zhang et al, 2022). More research is needed to develop more school-level theory-informed implementation strategies to promote staff's shared supportive beliefs about EBPs that entail school-level implementation, although emerging research exists on such implementation strategies at the individual level.…”
Section: Mediational Mechanism Of Change Underlying Educators' Belief...mentioning
confidence: 99%
“…These implementation strategies were based on social–cognitive principles of saying is believing, commitment and consistency, and social proofing (Cialdini, 2001). School-based research has indicated that, when teachers participated in activities designed to improve their behavioral and normative beliefs about implementing an EBP before attending training about the EBP, they exhibited improved intentions and intervention fidelity in their subsequent delivery of the EBP (e.g., Zhang et al, 2022). Regarding behavioral beliefs and attitudes, saying is believing indicates that, when individuals publicly advocate for a behavior, they often modify their own beliefs and attitudes toward that behavior to align with their commitment, even if their initial views were different (Aronson et al, 2002).…”
Section: Implementation Of Swpbismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, pre-implementation enhancement strategies 20,21 are particularly relevant for the Preparation phase. Pre-implementation enhancement strategies are delivered prior to the active implementation phase, with the goal of enhancing the impact of implementation-phase strategies.…”
Section: Recommendation 1: More Use Of Implementation Strategies At T...mentioning
confidence: 99%